1980
DOI: 10.1111/j.1744-7348.1980.tb03899.x
|View full text |Cite
|
Sign up to set email alerts
|

Hedgerow hawthorn (Crataegus spp.) and blackthorn (Prunus spinosa) as hosts of fruit tree viruses in Britain

Abstract: S U M M A R YApple chlorotic leafspot virus (CLSV) was detected in 27 of 109 hawthorn and three of 67 blackthorn plants sampled in various parts of Britain. The CLSV isolates possessed similar properties to those isolated from other rosaceous species but differed in the severity of symptoms they induced in woody indicators. No seed or aphid transmission of CLSV was detected.Prunus necrotic ringspot (PNRV) and prune dwarf (PDV) viruses were detected in four and three respectively of 67 blackthorn plants. The PN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Apple chlorotic leaf spot virus (ACLSV), the type member of the genus Trichovirus , is an important plant pathogen due to its worldwide distribution and broad host range, which includes cultivated, ornamental and wild species within the family Rosaceae (Al Rwahnih et al ., ). Even though it is often latent in cultivated pome fruit species, ACLSV causes serious diseases in stone fruit trees, while its presence has also been established in several wild and ornamental species (Peña‐Iglesias & Ayuso, ; Sweet, , ,b; Rana et al ., ). The complete genome sequence of several ACLSV isolates has been determined (German‐Retana et al ., ; Marini et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Apple chlorotic leaf spot virus (ACLSV), the type member of the genus Trichovirus , is an important plant pathogen due to its worldwide distribution and broad host range, which includes cultivated, ornamental and wild species within the family Rosaceae (Al Rwahnih et al ., ). Even though it is often latent in cultivated pome fruit species, ACLSV causes serious diseases in stone fruit trees, while its presence has also been established in several wild and ornamental species (Peña‐Iglesias & Ayuso, ; Sweet, , ,b; Rana et al ., ). The complete genome sequence of several ACLSV isolates has been determined (German‐Retana et al ., ; Marini et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…1). This is the first characterization of ACLSV infecting pear plants in Taiwan. ACLSV infections by mechanical inoculation have been reported in apple (Lister et al, 1965;Saksena and Mink, 1969), pear (Nemec, 1967;Pfaeltzer, 1962), plum and hawthorn (Sweet, 1980), cherry (Everett et al, 1993;Rana et al, 2008b), almond (Spiegel et al, 2005), and quince (Mathioudakis et al, 2007;Rana et al, 2007). It seems that the host range of ACLSV LTS1 is different from that of other reported ACLSV isolates.…”
Section: Discussionmentioning
confidence: 97%
“…Previously, ACLSV has been detected in apple and quince seedlings (Posnette & Cropley, 1964). ACLSV has also been detected in hedgerow‐grown hawthorn and blackthorn seedlings in the United Kingdom (Sweet, 1980). Mazeikiene et al (2018) reported that ACLSV occurs in old apple seedling trees.…”
Section: Discussionmentioning
confidence: 99%
“…ACLSV has been detected in hedges of Prunus spinosa and hawthorn seedlings ( Crataegus spp.) (Sweet, 1980). The only experimentally proven transmission pathway is through vegetative propagation of infected planting material (Šutić et al, 1999).…”
Section: Introductionmentioning
confidence: 99%